Google It Up! A Google Trends-based Uncertainty Index for the United States and Australia - Efrem Castelnuovo; Trung Duc Tran (Center for Economic Studies and ifo Institute (CESifo), 2017)
We develop uncertainty indices for the United States and Australia based on freely accessible, real time Google Trends data. Our Google Trends Uncertainty (GTU) indices are found to be positively correlated to a variety of alternative proxies for uncertainty available for these two countries. VAR investigations document an economically and statistically significant contribution to unemployment dynamics by GTU shocks in the United States. Differently, the contribution of GTU shocks to unemployment dynamics in Australia is found to be much milder and substantially lower than that of monetary policy shocks.
Keywords: C32; E32; E52; 330; Google trends uncertainty indices; uncertainty shocks; unemployment dynamics; VAR analysis